Formation mechanism of the U-shaped spectrum based on a simple plasma–dielectric–plasma (PDP) waveguide - Nie, Qiuyue; Wei, Guoqiang; Zhang, Zhonglin; Zhang, Zelin; Chen, Peiqi; Ai, Xin; Qian, Liang; Yan, Changshi (Frontiers in Physics, 2024)
Manipulating electromagnetic (EM) waves by PDP waveguides or plasma array structures presents significant potential in microwave signal processing, such as filtering, signal delay, EM enhancement or shielding, etc. Owing to simple structure and easy fabrication, the waveguide with a tooth-shaped resonator has been a strong candidate as a filtering device. Based on our previous U-shaped filtering excited by PDP waveguides with a double-teeth structure, in this work, the formation mechanism of a U-shape filtering spectrum is systematically explored by transmission-line theory (TLT) with proper field distributions. The results indicate that the U-shape spectrum consists of boundary edges and a filtering stopband. The boundary edges are attributed to Fano-type resonance, and the enhanced destructive interference from double teeth is responsible for the stopband. Such an approach shows a specific and clear mechanism for the generated U-shaped spectrum. In addition, the theoretical analysis of double teeth without Fano-type resonances is rigorously demonstrated using TLT, which makes a significant contribution to bandwidth modulation of stopband filtering in theory.These results contribute to understanding the formation mechanism of a U-shaped spectrum from a gap plasmon waveguide (such as PDP, or metal-insulator-metal (MIM), etc.) with tooth-shaped resonators, offering feasible direction for the optimization of filtering properties, as well as offering significant parameters for subsequent experiment design.